In vitro utilization of bio-active components from the underutilized fruits of Garcinia atroviridis for the suppression of Colletotrichum capsici - Mokhtar, Norhazwani; Siddiqui, Yasmeen; Syed Ali, Nusaibah (Friends Science Publishers, 2018)
Antifungal activities of the methanolic crude extracts of Garcinia atroviridis fruits were evaluated against Colletotrichum capsici, the causal pathogen of anthracnose of chilli.The antifungal activity of crude methanolic fruit extracts of G. atroviridis using poison food technique recorded 100% inhibition at minimum inhibitory concentration (MIC) values above 500 μg mL⁻ ¹.Similarly, percentage inhibition of 70.5% was calculated in agar well at 900 μg mL-1 which was at par with fungicide,Dithane® M-45 (73.8%) at 1000 μg mL⁻ ¹. It was accompanied by a significant reduction in cellulolytic and pectinolyticenzymes production by C. capsici at different concentrations. Several bioactive compounds in the crude extracts were identified using bioautography and LCMS. Amongst all, fatty acid (dodecanoic acid), hydrocoumarins, anthraquinones and benzofuran were prominent in suppression of C. capsici as evident from inhibition zone of 0.45 cm, 0.5 cm, 0.47 cm and 0.7 cm, respectively. Exposing the sporangial suspension of C. capsici to crude extract at increasing concentrations led to leakage of sugars and electrolytes. This eventually caused collapse and shrinkage of the spores and mycelium as visible under scanning electron microscope. Based on the findings, crude methanolic extracts of fruits from G. atroviridis may be developed as a potential botanical fungicide as an alternative to conventional methods to suppress anthracnose disease in chilli. © 2018 Friends Science Publishers